{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

# 2010 asm - Solutions for Assignment#1 1.2(7 Note that the...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Solutions for Assignment #1 1.2 (7) Note that the general solution of the differential equation is p ( t ) = 900 + Ce t 2 . (a) We need to find t such that p ( t ) = 0. First we solve for C . Since p (0) = 850 we get 850 = 900 + C , so C =- 50. We therefore need to find t such that 900- 50 e t 2 = 0. This means solving e t 2 = 18 . We take the logarithm of both sides and eventually get t ≈ 5 . 8 months. (b) If p (0) = p we solve for C to get C = p- 900. We then need to find t such that 900+( p- 900) e t 2 = 0, which means solving e t 2 = 900 900- p . We take the logarithm of both sides and eventually get t = 2ln 900 900- p months. (b) Remember that 1 years is 12 months so we need to find p that such p (12) = 0, i.e., 900 + ( p- 900) e 12 2 = 0 . This gives p = 900( e 6- 1). 1.3 (6) The equation is a linear equation of order 3. 1.3 (11) We simply need to substitute y 1 and y 2 into the differential equation and verify the right hand side equals the left hand side. We begin with y 1 ( t ) = t 1 / 2 . We first calculate the first two derivatives: y 1 = 1 2 t- 1 / 2 , y 00 1 =- 1 4 t- 3 / 2 . We then substitute these into the differential equation: l.h.s. = 2 t 2 y 00 1 + 3 ty 1- y 1 =- 1 2 t 1 / 2 + 3 2 t 1 / 2- t 1 / 2 = 0 = r.h.s., so y 1 is a solution. Similarly for y 2 ( t ) = t- 1 , we first calculate its first two derivatives: y 2 =- t- 2 , y 00 2 = 2 t- 3 , And then substitute into the differential equation: l.h.s. = 2 t 2 y 00 2 + 3 ty 2- y 2 = 4 t- 1- 3 t- 1- t- 1 = 0 = r.h.s., so y 2 is also a solution. 1 2.1 (17) We first find the general solution of the differential equation y- 2 y = e 2 t . This is already of the form y + p ( t ) y = g ( t ) with p ( t ) =- 2. This means we take our integrating factor μ ( t ) to be μ ( t ) = e R (- 2) dt = e- 2 t . If we multiply the equation by μ we know we can solve it as follows. d dt ( e- 2 t y ) = e- 2 t e 2 t ⇒ d dt ( e- 2 t y ) = 1 ⇒ Z d dt ( e- 2 t y ) dt = Z dt ⇒ e- 2 t y = t + C ⇒ y = Ce 2 t + te 2 t . We have shown that y = Ce 2 t + te 2 t , where C is an arbitrary constant, is the general solution of the differential equation y- 2 y = e 2 t . We now use the initial condition y (0) = 2 to determine the constant C . At t = 0 we have C + 0 = 2 ⇒ C = 2 . The solution of the initial value problem is therefore y ( t ) = 2 e 2 t + te 2 t . 2.1 (31) We first find the general solution of the differential equation y- 3 2 y = 3 t + 2 e t . We take the integrating factor μ ( t ) to be μ ( t ) = e R (- 3 2 ) dt = e- 3 2 t . We then solve the equation: d dt ( e- 3 2 t ) = e- 3 2 t (3 t + 2 e t ) ⇒ d dt ( e- 3 2 t y ) = 3 te- 3 2 t + 2 e- 1 2 t ⇒ Z d dt ( e- 3 2 t y ) dt = Z 3 te- 3 2 t + 2 e- 1 2 t dt ⇒ e- 3 2 t y =- 2 te- 3 2 t- 4 3 e- 3 2 t- 4 e- 1 2 t + C ⇒ y = Ce 3 2 t- 2 t- 4 3- 4 e t ....
View Full Document

{[ snackBarMessage ]}

### Page1 / 13

2010 asm - Solutions for Assignment#1 1.2(7 Note that the...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online